An Investigation of Canadian Undergraduate Music Education Students' Personal and Professional Experiences During a Three-Month Residency in China - Jonathan G. Bayley; Vanessa A. Mio (University of Windsor, 2020)
The present study investigated undergraduate Canadian music education students' personal and professional experiences during a three-month residency in China. Participants (N=3), in this case study, were part of a SSHRC funded Canada-China Reciprocal Learning Program and were in the process of completing a Bachelor of Education degree. The participants observed classroom teaching, attended workshops/presentations at Southwest University in Chongqing, China, and gave presentations to Chinese teachers and students. They were asked a wide range of open-ended questions relating to their preconceptions of life in China, coping strategies (e.g., language, local customs, environmental context, etc.), curricular and pedagogical similarities/differences, relationships with their Chinese counterparts, and potential impact on their future educational and professional plans. The findings indicated intellectual, social, and personal growth over this three-month period. Students spoke of overcoming fear and acquiring increased personal/professional self-awareness. However, there was no solid assurance that the participants' experiences would have a lasting positive effect on their future pedagogical practices.